Checklist and distribution of Carabidae Latreille, 1802 and Cicindelidae Latreille, 1802 (Insecta: Coleoptera) of El Salvador - Pablo-Cea, José D.; Cerón-Gómez, Rafael; Alfaro, Elizabeth; Wiesner, Jürgen (Zootaxa, 2024)
A paucity of knowledge regarding species distribution is one of the main shortfalls in large-scale biodiversity studies. This shortfall results in distribution maps of species that largely reflect sampling effort. Ground beetles (Carabidae) and tiger beetles (Cicindelidae) are among the most diverse and conspicuous families within the Order Coleoptera. However, no previous studies of these families have been published for El Salvador. Based on a literature revision, field work, and several entomological collections, the present article aims to describe the current state of knowledge of Carabidae and Cicindelidae occurrence in El Salvador. Eight subfamilies, 17 tribes, 35 genera, and 66 species are reported from the country; including a new country record of Eurycoleus macularius. We present a local distribution map for each species with available records. Our final aim is to stimulate interest in developing further studies that explore the taxonomic and ecological aspects of Carabidae and Cicindelidae in El Salvador.